Carbon Emission Disclosure: Relation to Environmental Performance, Carbon Performance, Company Size and Board Diversity (E-Jurnal Akuntansi, 2026)
The research aims to measure the impact of environmental performance, carbon performance, company size, and board diversity on the disclosure of carbon emissions. The samples were determined based on a quantitative purposive sampling method with a list of energy companies that have published the 2020-2022 Annual Report and Sustainability Report on the IDX with the acquisition of 18 samples. Multiple regression analysis is a method for measuring research hypotheses using SPSS v.25 statistical software. The results of this research show that the diversity of foreign boards and the diversity of board educational backgrounds influence the disclosure of carbon emissions. Meanwhile, carbon emissions disclosure cannot be influenced by environmental performance, carbon performance, board gender diversity and company size.
Keywords: Board Diversity; Carbon Performance; Company Size; Carbon Emission Performance.